2005
DOI: 10.1086/444487
|View full text |Cite
|
Sign up to set email alerts
|

Astrometric Methods and Instrumentation to Identify and Characterize Extrasolar Planets: A Review

Abstract: I present a review of astrometric techniques and instrumentation utilized to search for, detect, and characterize extra-solar planets. First, I briefly summarize the properties of the present-day sample of extrasolar planets, in connection with predictions from theoretical models of planet formation and evolution. Next, the generic approach to planet detection with astrometry is described, with significant discussion of a variety of technical, statistical, and astrophysical issues to be faced by future ground-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
68
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 235 publications
(366 reference statements)
1
68
0
Order By: Relevance
“…Astrometry is the oldest technique for indirect detection of extrasolar planets but has not yielded any results [2]. It requires looking for small perturbations in the position of a parent star [3].…”
Section: Indirect Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Astrometry is the oldest technique for indirect detection of extrasolar planets but has not yielded any results [2]. It requires looking for small perturbations in the position of a parent star [3].…”
Section: Indirect Detectionmentioning
confidence: 99%
“…Ground-based astrometry is usually done with an interferometer and could potentially find small (Earth-size) planets. An excellent review of work in this area can be found in Sozzetti [2].…”
Section: Indirect Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…To detect the barycentric motion of a nearby Sun-like star caused by a close Jupitermass planet, an astrometric accuracy of better than one milliarcsec (mas) per measurement is needed (Black & Scargle 1982;Sozzetti 2005;). At present, only a few instruments are capable of satisfying this requirement.…”
Section: Introductionmentioning
confidence: 99%
“…It will constitute a challenge to correctly identify sig nals with amplitude close to the measurement uncer tainties, particularly in the presence of larger signals induced by other companions and/or sources of astro physical noise of comparable magnitude. Finally, in cases of multiple component systems where dynami cal interactions are important, fully dynamical New tonian fits involving an n body code might have to be used to properly model the Gaia astrometric data and to ensure the short and long term stability of the solution (Sozzetti, 2005). …”
mentioning
confidence: 99%